Transitions to tertiary education: Measuring and minimising inequality between private and public school students in a university outreach program - McKenzie, Lara; Crawford, Nicole; Jaquet, Alison (2013)
Much of the literature concerned with evaluating public and private schooling focuses upon year 12 examination results. Investigating the transition to university, some studies have compared these results with first-year university marks. Very few researchers, however, have looked beyond students’ marks. This paper examines how “school type” affects student performance, participation, and experience in a university outreach program – SmARTS. SmARTS is run through The University of Western Australia’s (UWA) Faculty of Arts, Humanities, and Social Sciences (FAHSS). It engages year 11 students in a six-month research project, facilitated by the use of both e-learning and more traditional face-to-face methods. This paper is based on research that evaluated the 2009, 2010, and 2011 programs. The methods employed include analyses of student completion rates and results, as well as 198 student surveys, ten school coordinator surveys, and three group interviews with tutors. Based on schools’ socio-economic backgrounds, fees, and examination results, we have divided schools into four types: top-tier private, second-tier private, top-tier public, and second-tier public. Our findings suggest that top-tier private and top-tier public school students have the highest levels of participation, the lowest drop-out rates, and gain the highest results in SmARTS, while the opposite is evident for second-tier public school students. We also found, however, that second-tier public school students reported to have gained more generic skills from the program than did other groups. Our findings suggest that analysing examination results provides only a limited picture of how students experience the transition to university. We argue that through research and practice such as ours, inequalities can be more accurately measured, and thus minimised, before students enter university.